Ru'yatullah In Theological Tafsir Comparative Study Tafsir Tanzih Al-Qur'an Al-Mata'in And Ta'wilat Ahl Sunnah - Utari Nursyafitri; Putroe Balqis (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
The tendency of faith will affect the interpretation of the verses of ru'yatullah. Abdul al-Jabbar was a believer in Mu'tazilah and was fanatical towards the verses of ru'yatullah. According to him, Allah is impossible to see. Meanwhile, Abu Mansur al-Mapurid, a Sunni believer, rejected the opinion of Mu'tazilah on the issue of ru'yatullah theology. According to him, seeing Allah in the hereafter is possible. The difference of opinion between the two is due to different backgrounds. This study aims to find out the background of differences in interpretation. To achieve this goal, this study uses a qualitative method with content analysis as a data analysis tool. This study found that differences in interpretation can occur due to differences in the schools adhered to. The two mufassir in interpreting still adhere to their respective flows. Al-Jabbar for the sake of defending his teachings, namely Mu'tazilah. Meanwhile, al-Maturidi defended the faith he adhered to, namely ahl al-Sunnah wa al-Jama'ah, Maturidiyah.